2019
DOI: 10.1016/j.ajogmf.2019.100030
|View full text |Cite
|
Sign up to set email alerts
|

Food glycemic index changes in overweight/obese pregnant women enrolled in a lifestyle program: a randomized controlled trial

Abstract: BACKGROUND:The calculation of the glycemic index of food mirrors a rise in blood sugar levels. A loweglycemic index carbohydrate diet in pregnancy has been associated with normal infant birthweight. Thus, strategies to lower the food glycemic index could be successful in improving pregnancy outcomes. OBJECTIVE: The purpose of this study was to compare different prescribed diets on food glycemic index intake and its relationship with rate of large-for-gestational-age infants. STUDY DESIGN: At the 9the12th week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Moreover, a secondary analysis from three trials reported that the same dose of MI supplementation in women at risk for GDM affected birthweight, reducing the rate of both macrosomic newborns and LGA babies [67]. Such neonatal impact agrees with the evidence that dietary glycemic index directly correlates with LGA in newborns [68] and indirectly demonstrate that MI supplementation improves glycemic control in those pregnancies. Finally, in a condition where insulin-resistance is pathogenetic like PCOS, the beneficial effects of MI supplementation on hormonal and reproductive disturbances [20] were specifically reported also in pregnancy, where GDM rate was reduced [69].…”
Section: Insulin Sensitizerssupporting
confidence: 68%
“…Moreover, a secondary analysis from three trials reported that the same dose of MI supplementation in women at risk for GDM affected birthweight, reducing the rate of both macrosomic newborns and LGA babies [67]. Such neonatal impact agrees with the evidence that dietary glycemic index directly correlates with LGA in newborns [68] and indirectly demonstrate that MI supplementation improves glycemic control in those pregnancies. Finally, in a condition where insulin-resistance is pathogenetic like PCOS, the beneficial effects of MI supplementation on hormonal and reproductive disturbances [20] were specifically reported also in pregnancy, where GDM rate was reduced [69].…”
Section: Insulin Sensitizerssupporting
confidence: 68%
“…The lifestyle intervention implemented in this study included a low glycemic index, a low-fat hypocaloric diet, moderate physical activity, and specific timing of meals. These interventions were proven to effectively reduce the diet glycemic index (GI) of pregnant women [11]. GI is a measure repeatedly associated with improved perinatal outcomes [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…According to comprehensive meta-analysis, clinical relevance was of minor impact, mainly due to variations in the quality of trials, characteristics of the interventions, and assessed populations and outcome definitions between trials [9]. In two previously reported small trials, a hypocaloric-low-glycemic-index diet associated with increased physical activity significantly reduced gestational weight gain (GWG) and GDM rate in overweight/obese women [10,11]. In this study, we aim to evaluate if those clinical improvements could also benefit perinatal outcomes in the subgroup of women showing insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…After eliminating duplicate articles, the titles and abstracts were read by two researchers independently (Naiara Franco Baroni and Nayara Ragi Baldoni), minimizing possible bias in the selection and exclusion of the studies. In this stage, contact was made via e-mail with the authors to formally request the publications in full [32,33]. In the eligibility stage, a third researcher (Lívia Castro Crivellenti.)…”
Section: Study Selectionmentioning
confidence: 99%